Enhanced sliding mode controller performance in DC-DC buck converter using a tan hyperbolic reaching law and constant plus proportional reaching law - Siddesh K. B.; Basavaraja Banakara; R. Shivarudraswamy (Bulletin of Electrical Engineering and Informatics, 2020)
This paper presents an enhanced sliding mode controller (SMC) operation, chattering analysis and loading conditions of the SMC DC-DC buck converter. Sliding mode portion, chattering attenuation are analyzed by using a conventional and proposed reaching law in buck converter. A proposed tan hyperbolic reaching law (THRL) is originated to be useful in terms of chattering mitigation and fast convergence. The major drawback of the conventional reaching law viz, it bypasses the main portion of the sliding mode portion to ensure fast reaching. It causes more chattering, more time to reach the steady state on the switching surface. The most significant improvement of SMC is that it guarantees strengthening the sliding mode phase. The proposed tan hyperbolic reaching law is being hit here during an exponential adjustment so that the attributes of it, covers complete sliding mode portion, chattering mitigation and fast reaching time. In turn, cause fewer switching loss in the buck converter. Even external disturbances and uncertainty of the system occurs. The loading conditions are applied to proposed tan hyperbolic reaching law and analyzed. Simulation analysis conducted by MATLAB/Simulink.